2016
DOI: 10.4103/2008-7802.181759
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between cutaneous malignant melanoma and other cancers: An ecological study in forty European countries

Abstract: Background:The presence of noncutaneous neoplasms does not seem to increase the risk of cutaneous malignant melanoma; however, it seems to be associated with the development of other hematological, brain, breast, uterine, and prostatic neoplasms. An ecological transversal study was conducted to study the geographic association between cutaneous malignant melanoma and 24 localizations of cancer in forty European countries.Methods:Cancer incidence rates were extracted from GLOBOCAN database of the International … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…The lack of previous associations for prostate cancer and lymphatic/haematologic malignancy suggests that these findings should be considered hypothesis-generating and provide future avenues for research. In contrast, previous studies have provided some evidence for a relationship with family history of melanoma and adult testicular cancer (Hemminki and Chen, 2006; Larson et al , 2007; Serrano et al , 2016). In support of our previous findings suggesting an elevated risk of melanoma in relatives of paediatric GCT cases (Poynter et al , 2010), we observed an elevated risk of melanoma in male relatives of probands and an elevated, but non-significant risk of melanoma in female relatives of probands.…”
Section: Discussionmentioning
confidence: 71%
“…The lack of previous associations for prostate cancer and lymphatic/haematologic malignancy suggests that these findings should be considered hypothesis-generating and provide future avenues for research. In contrast, previous studies have provided some evidence for a relationship with family history of melanoma and adult testicular cancer (Hemminki and Chen, 2006; Larson et al , 2007; Serrano et al , 2016). In support of our previous findings suggesting an elevated risk of melanoma in relatives of paediatric GCT cases (Poynter et al , 2010), we observed an elevated risk of melanoma in male relatives of probands and an elevated, but non-significant risk of melanoma in female relatives of probands.…”
Section: Discussionmentioning
confidence: 71%